Plurilingual lecturers in English medium instruction in the Netherlands: the key to plurilingual approaches in higher education?. Issue 3 (3rd July 2019) - Duarte, Joana; van der Ploeg, Mara
ABSTRACT: Recent research calls for a re-structuring of higher education (HE) beyond English medium orientations by acknowledging the plurilingual resources of students and lecturers. In the Netherlands there is a rapid rise in plurilingual lecturers. The central question is to what extent these lecturers make use of their plurilingual resources for teaching within EMI and in what ways they can contribute to making EMI more plurilingual. This mixed-methods study aims at addressing this issue from the perspective of the lecturers. Based on 54 surveys and 20 qualitative interviews, it explores how Dutch-speaking and plurilingual lecturers use their plurilingual resources in EMI. Overall, whereas the plurilingual lecturers engaged more frequently in plurilingual practices in their lectures, Dutch-speaking lecturers were mostly concerned with the status and the level of proficiency in the Dutch language and often followed a strict interpretation of official language policies which limited their engagement with students' plurilingual resources. The study highlights the ways in which plurilingual lecturers can contribute to a shift within EMI towards acknowledging and using the plurilingual resources of both lecturers and students.